Improving The Force Delivery Trend Of Nickel-Titanium Archwire In Orthodontic Bracket System - Latiffi, Nur Ainul Nurina Ishak (Universiti Sains Malaysia, 2019)
Orthodontics is a specialty within dentistry that focus on correcting bites, and the position of the teeth. In such cases, orthodontic treatments are recommended to slowly change the positioning and correcting the teeth to be straighter and more aligned using devices such as braces. Dental braces usually consist of brackets that are bonded to the teeth and an archwire that is inserted into the brackets. This study was designed to investigate the influence of the orthodontic bracket system toward the effective force release by NiTi archwire during orthodontic leveling treatment. The force-deflection curve of superelastic NiTi archwires bends in three-bracket configurations were predicted by three-dimensional finite element model integrated with superelastic user material subroutine and contact interaction that resembled the actual three bracket bending test that conducted using a universal testing machine. The competency of the bending model was examined by comparing the predicted force-deflection curve with the experimental result and three different sets of bracket dimensions. It was found that the wider bracket produce a greater slope while narrow bracket helps in reducing the force slope on the unloading cycle. Besides, the friction between the wire and the bracket increased proportionally as a function of wire deflection, hence the bracket altered the constant force behavior of NiTi archwire material into slope.